3D printing of biological tooth with multiple ordered hierarchical structures - Menglu Zhao; Yanan Geng; Suna Fan; Xiang Yao; Jiexin Wang; Meifang Zhu; Yaopeng Zhang (Materials Today Bio)
Natural teeth fulfill functional demands by their heterogeneity. The composition and hydroxyapatite (HAp) nanostructured orientation of enamel differ from those of dentin. However, mimicking analogous materials still exhibit a significant challenge. Herein, a bottom-up, sequential approach was formulated by combining shear-induced and magnetic-assisted 3D printing technology, enabling the fabrication of the intricate microstructure of a multi-material dental crown, where the HAp nanostructure is highly ordered and almost perpendicular to each other at the dentinoenamel junction (DEJ). The HAp nanorods were first induced to achieve high orientation in each printed line, then formed a plane with a vertical structure of DEJ under the shear force and magnetic field at dentin and enamel, respectively, and finally 3D-printed into a dental crown with bilayered parts exhibiting site-specific composition, texture, and outstanding biocompatibility. This novel approach can be applied to design and fabricate natural tooth crowns, indicating the potential for multi-level and multi-dimensional texture control.